Inhibition of Akt and other AGC kinases: A target for clinical cancer therapy?. (February 2018) - Prêtre, Vincent; Wicki, Andreas
Abstract: AGC kinases have been identified to contribute to cancer development and progression. Currently, most AGC inhibitors in clinical development are Akt inhibitors such as MK-2206 or GDC-0068, which are known to promote cell growth arrest and to sensitize cancer cells to radiotherapy. Response rates in clinical trials with single agent Akt inhibitors are typically low. The observed adverse events are within the expected limits for compounds inhibiting the PI3K-mTOR axis. Preclinical and early clinical data for combination therapies are accumulating. Based on these data, several Akt inhibitors are about to enter phase 3 trials. Besides drugs that target Akt, p70S6K inhibitors have entered clinical development. Again, the response rates were rather low. In addition, relevant toxicities were identified, including a risk for coagulopathies with these compounds. Multi-AGC kinase inhibitors are also in early clinical development but the data is not sufficient yet to draw conclusions regarding their efficacy and side-effect profile. PKC inhibitors have been tested in the phase 3 setting but were found to lack efficacy. More trials with isoform-specific PKC inhibitors are expected. Taken together, therapies with AGC kinase inhibitors as single agents are unlikely to meet success. However, combination therapies and a precise stratification of patients according to the activation of signaling axes may increase the probability to see relevant efficacy with these compounds. The emergence of onco-immunotherapies holds some new challenges for these agents.